Pengaruh Proporsi Komisaris Independen dan Komite Audit terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Chessara Addina; Hendra Harmain; Rahmi Syahriza (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to determine the effect of the proportion of independent commissioners and audit committees on financial performance in manufacturing companies listed on the Indonesia Stock Exchange partially and simultaneously. This research uses quantitative methods with an associative approach. The results of this study showed that partially the proportion of independent commissioners did not have a significant effect on financial performance with the tcount < ttable (0.561015 < 1.97569) and the probability value showing a number greater than the significance value (0.5758 > 0.05). Meanwhile, the audit committee has a significant effect on financial performance with the tcount > ttable (7.265215 > 1.97569) and the probability value showing a number smaller than the significance value (0.0000 < 0.05). Simultaneously, the proportion of independent commissioners and audit committees has a significant effect on financial performance with the Fcount > Ftable value (13.81392 > 3.06) and a probability value showing a figure of 0.000000 which means it smaller than the significance value of 0.05 (0.000000 < 0.05). Financial performance can be explained by the proportion of independent commissioners and audit committees of 78.37%, while the remaining 21.63% is explained by other factors beyond the variables studied. Keywords: The Proportion of Independent Commissioners, Audit Committees, Financial Performance